Five-canal maxillary first molar with calcified MB2 and low bifurcation of distal root canals: a case report - Lin, Xuandong; Xie, Hongyu; Ruan, Sijie; Ma, Xueling; Long, Jindong; Xie, Fangfang (Frontiers in Oral Health, 2025)
Root canal therapy is a highly regarded procedure, and failure to recognize the extremely variable anatomy of the maxillary first molars leads to unpredictable outcomes. This study reports the exceedingly rare case of a 27-year-old male with a maxillary first molar with one palatal and four buccal canals, and low bifurcation of the two distal root canals. The patient underwent nonsurgical endodontic treatment (root canal therapy), the buccal apical fistula and swelling disappeared completely, and imaging findings revealed a reduction of the apical shadow area. The patient did not experience a relapse during the 6-month follow-up period. This report suggests if thin root canal is not consistent with the root diameter, redundant root canals and low bifurcation should be considered. In maxillary first molars, it is important to find mesiobuccal 2 in the calcified root canal, still, using cone-beam computed tomography is essential for the exploration and evaluation of additional root canals, such as distobuccal 2, to prevent misdiagnosis.